Persona Manifestasi Diri pada Lirik Lagu dalam Album Ini Bukan Nosstress Karya Nosstress: Kajian Estetika - Pangesti, Shafa; Purnomo, Mulyo Hadi; Fadilah, Yuniardi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2024)
The purpose of this study is to reveal the form of manifestation through aesthetic means in the lyrics in the album Ini Bukan Nostress by Nosstress. This qualitative descriptive study uses an objective method with listening and noting techniques. The data taken is in the form of three of the nine song lyrics in the album. The results of this study are the discovery of aesthetic concepts through the perception of meanings depicted by the lyrical